Model Integratif Literasi Asesmen Guru melalui Participatory Action Research di Madrasah Ibtidaiyah - Muhamad Amin; Febriarsita Eka Sasmita (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2023)
This study aims to reconstruct teacher assessment literacy in Islamic Elementary Schools (Madrasah Ibtidaiyah) through a Participatory Action Research (PAR) approach by developing an integrative and contextual capacity-building model. The research locus was conducted at MI Toriqussalam and MI NU Kureksari, involving teachers as subjects and collaborative partners in three action cycles, including planning, implementation, observation, and reflection. The research findings show a significant transformation in the implementation of teacher assessment, characterized by increased ability to develop operational indicators, the development of authentic assessments, the use of learning outcome data as a basis for learning decision-making, and the integration of Islamic values ​​in assessment instruments. The reflective and collaborative process in PAR has been shown to shift the assessment paradigm from merely administrative to diagnostic and transformative. Furthermore, this study produces an integrative literacy model for teacher assessment that combines the dimensions of authentic assessment, data literacy, and the internalization of Islamic values ​​as a conceptual contribution to the development of learning evaluation practices in Islamic elementary education.